Muslim women in the economy
1 online resource.
Keywords: "This book explores the changing role of Muslim women in the economy in the twenty first century. Sociological developments such as secular education, female-focused policies, national and global commitments to gender equality as well as contemporary technological advances have all served to shift and redefine the domestic and public roles of Muslim women, leading in many places to increases in workplace participation and entrepreneurship. This book investigates the contexts of these shifts and the experiences of women balancing faith and other commitments to actively engage in the economy in vastly different countries. The book looks at how family codes and the understandings of Muslim male and female roles sit alongside social and economic advances and the increases in women partaking in the economy. Within a globalised world, the book also highlights the importance of the implementation of the current sustainable development priorities in the context of Muslim societies, including Sustainable Development Goal 5 that focuses on the vital role of women and their full participation in all areas of sustainable development. With cases ranging from Saudi Arabia, Iran, Bangladesh, Pakistan, Indonesia, Nigeria, Kenya through to Spain, Bulgaria and Australia, Muslim Women in the Economy will be of considerable interest to those studying, researching and interested in gender, development, and religious studies"--